2021
DOI: 10.1177/23259582211066401
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Empirical Literature on Peer Support for People Living with HIV

Abstract: People living with HIV receiving antiretroviral therapy need support related to linkage to care and self-management in everyday life. Peer support has been found to provide varied support according to the unique needs of the group. This scoping review aims to provide an overview of research on peer support provided to people living with HIV. A search was conducted in eight databases until May 2021, and two reviewers independently screened all identified studies. We sorted the included studies into categories a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Although the effectiveness of a range of peer support interventions has been studied, a recent review [ 33 ] demonstrated a scarcity of studies that explored experiences with peer support from the receiver’s perspective. The results of the review indicated multiple benefits of meeting a peer supporter, necessitating a clarification of the peer support provided to PLHIV as a CLLC.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effectiveness of a range of peer support interventions has been studied, a recent review [ 33 ] demonstrated a scarcity of studies that explored experiences with peer support from the receiver’s perspective. The results of the review indicated multiple benefits of meeting a peer supporter, necessitating a clarification of the peer support provided to PLHIV as a CLLC.…”
Section: Introductionmentioning
confidence: 99%
“…Using this score to predict likelihood of unsuppressed viral load at the beginning of treatment and tailoring scheduled clinic visits to predicted viral load suppression will reduce the cost of treatment for people on care for the first 18 months. Currently, Kenya employs several evidence based interventions in supporting adherence including community based support groups and individual level support through peer champions or peer navigators [ 14 ]. Use of this empiric scoring tool will alleviate the burden on patients and reduce the strain on the public health system by allowing clinicians to reduce the time spent with patients predicted to have suppressed viral load while focusing intensified adherence support to those predicted to be virally unsuppressed.…”
Section: Discussionmentioning
confidence: 99%
“…Future research likely involves testing an intervention that includes telemedicine and/or peer support as strategies to facilitate HIV care engagement examining dual outcomes of treatment initiation and care retention among rural PWH. Based on a recent scoping review of peer support for PWH, research on the topic has increased in the last decade and yet gaps in evidence warrant continued study 33 …”
Section: Discussionmentioning
confidence: 99%